2017
DOI: 10.1175/jpo-d-16-0193.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamical Relationship between Equatorial Pacific Surface Currents, Zonally Averaged Equatorial Sea Level, and El Niño Prediction

Abstract: Previous work has shown that for large zonal scales and low frequencies, wind-forced sea level, even near the equator, can be described by wind-forced long Rossby waves. In the eastern equatorial Pacific where the interannual wind forcing is small, these waves are essentially locally unforced and propagate westward from the boundary. At the boundary the waves’ sea level is in phase because of geostrophy and no normal flow to the boundary. However, because the waves propagate more slowly with increasing latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…We retain the first five baroclinic modes but will show that equatorial Pacific OHC interannual variations obtained from the first two modes reproduce most of the observed variations, in agreement with earlier studies (e.g. Chen et al 1995;Boulanger and Menkes 2001;Shu and Clarke 2002;Izumo et al 2016;Zhang and Clarke 2017).…”
Section: Lcs Modelsupporting
confidence: 87%
See 2 more Smart Citations
“…We retain the first five baroclinic modes but will show that equatorial Pacific OHC interannual variations obtained from the first two modes reproduce most of the observed variations, in agreement with earlier studies (e.g. Chen et al 1995;Boulanger and Menkes 2001;Shu and Clarke 2002;Izumo et al 2016;Zhang and Clarke 2017).…”
Section: Lcs Modelsupporting
confidence: 87%
“…Many past studies (e.g. Chen et al 1995;Boulanger and Menkes 2001;Shu and Clarke 2002;Izumo et al 2016;Zhang and Clarke 2017) have shown the importance of the second baroclinic mode for ENSO-related equatorial thermocline depth variations. Including the 2 nd baroclinic mode in our model increases the dominance of K f , since K f,2 is fast enough to be rather in-phase with K f,1 and amplifies it, while the slower R1 f,2 does not, being less in phase with R1 f,1 (not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower-correlation equatorial region between about 1658E and 1708W is influenced by an interannual shallow (50-70 m deep) freshwater jet that is fundamental to ENSO dynamics (Zhang and Clarke 2015). Because of the jet, the monthly anomalous sea level in this region has a contribution not only from thermocline variability, but also from the dynamic height z TF associated with the low-salinity jet.…”
Section: Equivalence Of Wwv Wwv Eq and Adjustedmentioning
confidence: 99%
“…Although there have been several theories relating El Niño/La Niña to the WWV (Jin 1997a,b;Clarke et al 2007;Fedorov 2010;Clarke 2010;Thual et al 2013;Neske and McGregor 2018), only recently (Zhang and Clarke 2017) has the direct linkage between the zonal equatorial flow and WWV begun to be appreciated. In this paper we will apply that relationship to understand the physics of why the WWV is a useful predictor of El Niño beyond the spring persistence barrier.…”
Section: Introductionmentioning
confidence: 99%